Surface microhardness and depth of cure of composite resin cured with LED and Halogen units (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the surface hardness and depth of cure ofresin composites cured with a quartz tungsten halogen (QTH) lamp or a light emittingdiodes (LED) unit.Swiss Tec (colten/whaledent AG, Switzerland) resin composite was placed in1, 2,3, and 4 mm depth and 8 mm width metallic molds and cured using the QTH light orthe LED unit for 40s.A total of 40 samples were made that divided into two groups according to thetype of curing light with 20 samples each. Each group was subdivided into 4 groupsaccording to the height of the mold with 5 samples each. Microhardnessmeasurements were performed using a calibrated Vickers indenter (100 g load and30s dwell time). Measurement of depth of cure was carried out by means of hardnessratio (bottom/top × 100).Results were analyzed by paired student's t-tests (P < 0.05). Results showed thatLED exhibited higher microhardness values than QTH unit and the difference wasstatistically significant (P = 0.03) at the top surface and highly significant (P = 0.001)at the bottom surface.Further more the results revealed that LED produced samples with hardness ratio(depth of cure) higher than QTH unit and the difference was highly significant (P =0.004) at 3 mm depth. Both curing lights inadequately cure samples at 4 mm depth.Conclusions: Curing effectiveness of resin composite is better with LED thanQTH unit especially when the composite thickness exceed 2 mm.